Structural and electronic properties of type I and VIII Sr8Ga16Sn30 clathrates under compression. (20th March 2016) - Wang, J.; Cheng, F.; Liu, H.; Li, D.; Shen, L.; Shen, K.; Deng, S.
Abstract : Based on the ab initio density functional theory under generalised gradient approximation, we calculated the total energy and band structure for the type I and VIII Sr8 Ga16 Sn30 under hydrostatic pressure, the results reveal that the type VIII Sr8 Ga16 Sn30 is the stable phase and the type I Sr8 Ga16 Sn30 is the metastable phase, and there is no phase transformation between the type I and VIII Sr8 Ga16 Sn30 under hydrostatic pressure. The type I and VIII Sr8 Ga16 Sn30 are indirect semiconductors with band gaps of 0.125 and 0.009 eV respectively. With increasing pressure, the band gaps are increased, and there is no significant change for the dispersion of band near the Fermi lever. The stability of Sr8 Ga16 Sn30 is lower than that of Ba8 Ga16 Sn30 ; therefore, it is more difficult in the synthesis of Sr8 Ga16 Sn30 compared to that of Ba8 Ga16 Sn30 .